Form And Function Shifting Of The Music Corps Bregada In Kasunanan Surakarta Palace (Jurnal Seni Musik, 2022)
Brigade or more known as the Javanese term of the bregada in Surakarta Kasunanan Palace has always experienced shifts or even form changing and function in the post-independence period of Indonesia. Even though there has been a shift in form and function, the Bregada of the Kasunanan Surakarta palace is still maintaining its existence. This study aims to describe the form and function shifting process of the bregada in Kasunanan Surakarta palace, especially the bregada of the music corps unitary. The focus discussed in this paper include: (1) Function shifting of the Kasunanan Surakarta Palace music corps, (2) repertoires songs changing that played by the Surakarta Kasunanan Palace music corps from the pre-independence to the Indonesian post-independence period, and (3) performance form changing of the Kasunanan Surakarta Palace music corps. This research data uses a literature review from historical records and ancient manuscripts, as well as in-depth interviews with key informants. Based on the study results, the function shifting of the music corps bregada and the songs that were played were visible from the function of war music turning into traditional and cultural activities, especially referring to the function as performing arts and tourism activists, that is the performance of a military music parade for the advancement of tourism in the Solo city, Central Java.